Anti-Regime Movement in the Second Half of the 20th Century in Soviet Ukraine: Essence, Scale, Forms and Methods of Resistance - Bazhan, Oleh (Genocidas ir rezistencija, 2023)
The article highlights the general trends and features of the formation of the opposition movement in Ukraine from the late 1950s through the 1980s, and examines the forms and methods of the protest movement as well as the specifics of the information and communication activities of Ukrainian dissidents. The study focuses on the mechanism of political repression, the use of criminal legislation in the Ukrainian SSR to punish dissent, and the approximate number of citizens of the republic who were repressed for “anti-Soviet propaganda and activities” from the 1950s through the 1980s.